The Investigation on Single Event Function Failure for DC/DC Converters with Three Single Terminal Topological Structures. Issue 6 (1st November 2016) - Li, Pengwei; Wang, Wenyan; Luo, Lei; Yu, Qingkui; Tang, Min; Du, Feipeng; Liu, Jie
Abstract : Heavy ion radiation experiments have been done to DC/DC converters with different topological structures for space applications. The test results were analyzed about the function failure of three topological structures caused by single event effects. The relationship between the function failure and the input supply voltage, the output load current and the topological structure of the module were discussed. Based on the analysis of the variation relationship among the source/drain terminal voltage of MOSFETs and the input voltage and the output load, the sensitivity factors associated with the function failure caused by single event effects were discussed. A new analysis on single event function failure of DC/DC converter based on different topologies has been presented, which can be applied to radiation hardened design and space application.